Episodic memory for natural and transformed food. (October 2018) - Aiello, Marilena; Vignando, Miriam; Foroni, Francesco; Pergola, Giulio; Rossi, Paola; Silveri, Maria Caterina; Rumiati, Raffaella I.
Abstract: It has been proposed that the conceptual knowledge of food and its putative subdivision into natural (i.e., fruit/vegetables) and transformed (i.e., food that underwent thermic or non-thermic processing) may follow the living/non-living distinction. In the present study, we investigated whether the advantage for living things compared to non-living things observed in episodic memory (the so-called animacy effect ) extends to natural foods and transformed foods respectively. We pursued this issue in two experiments. In Experiment 1, we measured episodic memory for natural and transformed foods in young participants. In Experiment 2, we enrolled dementia-free centenarians, patients with Alzheimer's disease (DAT), Progressive primary aphasia (PPA), and healthy controls whose episodic memory was also tested for living/non-living things. Results showed that young participants had better recognition memory for transformed foods compared to natural foods. This difference disappeared in centenarians and patients. However, centenarians and PPA exhibited enhanced levels of false alarms (FA) with natural food, and DAT patients with both natural and transformed food. As far as the living/non-living distinction is concerned, the episodic memory for the living category appears more resilient to the decline compared to the non-living category in patients, particularly those with PPA. In conclusion, our study shows that transformed food is better remembered than natural food, suggesting that it is more salient and possibly relevant from an evolutionary perspective. The natural/transformed distinction appears susceptible to erosion only in the presence of a high degree of episodic memory impairment. These results offer novel insight on episodic memory of food, and also extend the current knowledge on the animacy effect in episodic memory.